Efficient Pricing Technique for Resource Allocation Problem in Downlink OFDM Cognitive Radio Networks. (May 2017) - Abdulghafoor, O B; Shaat, M M R; Ismail, M; Nordin, R; Yuwono, T; Alwahedy, O N A
Abstract: In this paper, the problem of resource allocation in OFDM-based downlink cognitive radio (CR) networks has been proposed. The purpose of this research is to decrease the computational complexity of the resource allocation algorithm for downlink CR network while concerning the interference constraint of primary network. The objective has been secured by adopting pricing scheme to develop power allocation algorithm with the following concerns: (i) reducing the complexity of the proposed algorithm and (ii) providing firm power control to the interference introduced to primary users (PUs). The performance of the proposed algorithm is tested for OFDM- CRNs. The simulation results show that the performance of the proposed algorithm approached the performance of the optimal algorithm at a lower computational complexity, i.e., O ( N log N ), which makes the proposed algorithm suitable for more practical applications.